2008
DOI: 10.1002/bit.22083
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the α‐amylase from Geobacillus stearothermophilus US100 for detergent incorporation

Abstract: AmyUS100DeltaIG is a variant of the most thermoactive and thermostable maltohexaose forming alpha-amylase produced by Geobacillus stearothermophilus sp.US100. This enzyme which was designed to improve the thermostability of the wild-type enzyme has acquired a very high resistance to chelator agents. According to modeling structural studies and with the aim of enhancing its resistance towards chemical oxidation, a mutant (AmyUS100DeltaIG/M197A) was created by substituting methionine 197 to alanine. The catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Oxidation of the methionine residue situated in the cavity of the AmyK active site has been shown to decrease its activity or even inactivate the enzyme (11,33). The model structure of AmyK from Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxidation of the methionine residue situated in the cavity of the AmyK active site has been shown to decrease its activity or even inactivate the enzyme (11,33). The model structure of AmyK from Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…The compatibility of AmyK-p1 with the washing powders may be the result of ionic interactions and hydrophobic or hydrophilic interactions between the detergents and the fusion peptide (11). This might be explained by the fact that for liquid or laundry detergents, the physical isolation of enzymes was difficult and the presence of solvent (water) amplified the detrimental effects of surfactants due to the numerous surfactants in those detergents (11,35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used low-energy N + ion implantation to mutate the B. amyloliquefaciens strain RL, an important microbe (with roles in many aspects of industry, agriculture, environmental reclamation, pest control, etc.) that secretes a thermostable α-amylase, and screened for mutants with increased starch degradation activity (Declerck et al, 2000;Kim et al, 2003;Du et al, 2006;Khemakhem et al, 2009). We found that, compared to the parental strain, the mutant strain RL-1 excreted a highly thermostable α-amylase with 57.1% increased activity (58.51 U/mL).…”
Section: Discussionmentioning
confidence: 85%